Rapid maxilary expansion in young adults: comparison of tooth-borne and bone-borne appliances, a cohort study. - Victor Rojas; Catalina Macherone; Maria Ignacia Zursiedel; Juan Guillermo Valenzuela (Universidad de Concepción., 2019)
Introduction: Maxillary constrictions are one of the most frequent abnormalities, regardless of the type of dentition studied. They can be treated either with tooth-borne or bone-borne expander appliances, depending on the biological maturation of the patient. Treatment during prepubertal stages has been shown to be successful, but there is evidence of an open suture even in late adolescence stages. The aim of this study is to compare the effects of a rapid expansion bone-borne device to a tooth-borne device in young adults suffering from maxillary constriction, by means of Cone-Beam Computed Tomography. Materials and methods: A retrospective observational study was conducted in nine patients (three males, six females) with a mean age of 18±5.5 years, who attended the Dentistry Service of Universidad de Chile during 2014-2015. Six patients were treated with tooth-borne appliances (Hyrax type) and three patients with bone-borne appliances (MARPE). Linear measurements of the anterior and posterior transverse dimension and angular measurements of the inclination of molars and incisors were obtained through CBCT for each group in T1 and T2. Results: A significant increase in the posterior transverse dimensions in both groups was observed. Radiolucency of the suture was observed in all patients treated with miniscrews and in half of the patients treated with Hyrax. Greater angulation of molars was shown in the tooth-borne group in comparison with the bone-borne group. Conclusion: Both appliances caused an increase in the posterior transverse dimension, but bone anchored appliances achieved a more parallel and skeletal expansion. Randomized clinical trials with a larger sample and follow-up are needed.